Infectious bovine rhinotracheitis/infectious pustular vulvovaginitis (IBR/IPV) in cattle in central Ethiopia - Tekelye Bekele; Cecchini, G.; Kasali, O.B.; Scholtens, R.G.; Mukasa-Mugerwa, E. (1989)
Determines the prevalence of infections bovine rhinotracheitis/infections postular Vulvovaginitis (IBR/IPV) antibodies in cattle in central Ethiopia using the micro-enzyme-linked immunosorbent assay (ELISA) technique.